ABOUT THE TEACHING OF SPECIFIC INTEGRAL SUBJECTS IN GENERAL SECONDARY EDUCATION SCHOOLS AND SECONDARY SPECIAL VOCATIONAL EDUCATION INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In general, in the 11th grade of secondary education schools and secondary special, vocational educational institutions, when giving the subject of definite integral (also the subject of the function limit, which is used in the concept of definite integral), taking into account the above information, conclusions, and explaining the subject from the point of view of pedagogy: to whom, what, We would like to ask you to pay attention to the following suggestions and considerations while covering the topics with a more positive approach to the issue of giving in what content, in what volume and in what way.